Risk Factors for Sex Work Recidivism in Commercial Sexual Exploitation Victims - Falegan, Oluwatominsin O (2016)
INTRODUCTION: An estimated 4.9 million individuals worldwide are currently victims of some form of commercial sexual exploitation. Although there are differing opinions on what can be classified as commercial sexual exploitation, study findings demonstrate that the risk factors and health outcomes for individuals forced or who opt to enter sex work include mental illness, lack of social support, physical injuries and substance abuse. Although studies note that sex work recidivism may be an issue for victims who have exited the commercial sexual exploitation industry, literature addressing the cause and incidence of the phenomenon is very limited. AIM: The purpose of this study was to identify and explore possible risk factors for sex work recidivism by using factors noted in criminal recidivism that align with outcomes for commercial sexual exploitation. The author hypothesizes that individual level factors, such as mental health, substance abuse, and history of abuse, and relationship level factors, such as social support or the lack there of, will be discussed the most in the literature analyzed. METHODS: The researcher did a systematic search of terms related to commercial sexual exploitation (namely: prostitution and sex trafficking) in Georgia State University’s online library database and PubMed. Inclusion criteria for this project was the use of terms in an abstract or title and content addressing health outcomes of commercial sexual exploitation. Using an adaptation of the socio-ecological model, the researcher completed a content analysis on articles that met inclusion criteria and extracted and counted the most prevalent themes. Ultimately, the themes were categorized by the four levels of the socioecological model. RESULTS: Out of the 47 articles initially retrieved, 21 articles met the inclusion criteria. Individual and Societal level factors were mentioned in 20 of the 21 articles. Relationship level factors were mentioned in 17 of the 21 articles, and Community level factors were mentioned in 16 of the 21 articles. DISCUSSION: The findings supported the researcher’s hypothesis that individual level factors such as mental illness and substance abuse would be most prevalent in the studies analyzed. However, the findings demonstrating the equal prevalence of societal factors such as inequalities and economic instabilities was a deviation from the author’s predictions